Enhancing Learning of Electromagnetic Wave Propagation through 3D Visualization in Physics Education - Mahmudah, Muhammad Suryauno; Yacobi, Muhammad Abrar Asyrafy; Steeven, Daniel (MJI Publisher by PT Mitra Jurnal Indonesia, 2024)
This study aims to simulate the characteristics of electromagnetic wave propagation in different media, specifically focusing on water and oil, using Maxwell's wave equations. Water, acting as a conductor, and oil, as an insulator, were chosen to investigate the disparities in conductivity, attenuation constants, and their effects on wave propagation. The concept of electromagnetic wave propagation forms the basis for many advanced topics in physics, but is often challenging due to its abstract nature. Through these simulations, researchers observed temporal changes in electric and magnetic fields and visualized wave trajectories. These simulations allow for an extensive analysis without the need for physical wave transmission experiments. The integration of 3D visualization is a tool that can significantly improve students' concept understanding through visual and interactive representation of wave propagation. This research enhances theoretical understanding and has practical applications in areas such as underwater communications, oil spill monitoring, and measuring oil layer thickness. By employing the Finite-Difference Time-Domain (FDTD) method, the simulations demonstrated that variations in conductivity and attenuation constants considerably influence the behavior of electromagnetic waves. In oil, the waves retain their amplitude and phase during propagation, whereas in water, they experience attenuation, leading to a reduction in amplitude. These results offer valuable insights into the interaction of electromagnetic waves with various media, providing practical guidance for optimizing the performance of devices utilizing these waves.